De l’après-ski à l’après-tourisme, une figure de transition pour les Alpes ? - Philippe Bourdeau (Revue de Géographie Alpine)
Winter sports occupy a prominent place in European tourism, not only because of their economic importance in mountainous areas but also due to their major symbolic significance in the "leisure civilisation". Yet the world of winter tourism is full of uncertainties connected with climate change and also with evolutions and structural breaks that call into question the development model on which it is based. This context of profound change gives us the opportunity to question the limits of the industrial model that has governed the development of the Alps for the practice of skiing and to examine alternative future scenarios to "all-out skiing" and even "all-out tourism".